Affirmation-Tapping to Reduce Pain Perception and Glutamate Serum Levels of Post-cesarean Patients - Joko Suwito1 , Nursalam Nursalam2 , Agus Sulistyono3 , I Ketut Sudiana3 , Urged G. A. Suprabawati4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Affirmation, by praying and positive evaluation accompanied by acupoint stimulation, hasbeen shown to reduce pain in postoperative patients. In other studies, affirmations can reduce chronic paindue to the down-regulation performance of Glutamate receptors. Acupuncture can reduce pain complaintsby modulating Glutamate at the spinal level. So it is suspected that affirmation-tapping can reduce postsurgical pain due to modulation of Glutamate; however clinical studies have not been conducted. Theaim is to compare the pain perception of postoperative patients given affirmation-tapping therapy withother treatment patients as complementary nursing interventions. This is to see if the modulation of theperformance of serum Glutamate levels is different from other treatments. Methods: We used a randomizedpost-test control group design that was performed parallel in post-cesarean patients. A sample of 40 patientswas divided into four groups (10 in affirmations, 10 in tapping, 10 in affirmation-tapping and 10 in controls).They were obtained through simple random sampling. The instruments included affirmation-tapping guides,Elisa kits and McGill Melzack Pain’s short questionnaire form (MPQ-sf). The independent variable wasthe affirmation-tapping intervention and the dependent variable was the perception of pain and Glutamateserum level. Data were analyzed using simple linear regression. Results: The average of Glutamate levelsin the Affirmation-tapping treatment group was lower (0. 034±0. 004) pg/mL and significantly different(Sig=0.00) from other groups (0. 056±0. 011) pg/mL. Conclusion: Affirmation-tapping as a complementarynursing intervention decreases pain perception and Glutamate serum levels in patients post-cesarean sectionthat supports conventional treatment. Affirmation-tapping is recommended as an intervention to overcomepain perception in postoperative nursing patients who support conventional treatment.